1998
DOI: 10.1103/physrevb.58.3511
|View full text |Cite
|
Sign up to set email alerts
|

Native and radiation-induced photoluminescent defects inSiO2: Role of impurities

Abstract: We report photoluminescence ͑PL͒ data on amorphous SiO 2 in the spectral range of the ␣ ͑4.3 eV͒, ␤ ͑3.1 eV͒, and ␥ ͑2.7 eV͒ emissions excited with synchrotron radiation. Differently prepared and treated samples are compared. Neutron irradiation gives rise to PL features distinct from those observed both in unirradiated Ge-doped silica and in samples with other impurities. Our data suggest that the defect-formation processes determine the different PL patterns observed in SiO 2 , while the usually proposed dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
42
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 27 publications
(33 reference statements)
8
42
2
Order By: Relevance
“…Similar UV emission has been previously reported for Ge implanted SiO 2 film 4 and unirradiated SiO 2 film containing different impurities. 9 Oxygen deficient defects in SiO 2 with different environment are believed to result in different UV bands. 9 Tong et al observed adjustable UV emission bands from silicon rich oxide films.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar UV emission has been previously reported for Ge implanted SiO 2 film 4 and unirradiated SiO 2 film containing different impurities. 9 Oxygen deficient defects in SiO 2 with different environment are believed to result in different UV bands. 9 Tong et al observed adjustable UV emission bands from silicon rich oxide films.…”
Section: Discussionmentioning
confidence: 99%
“…9 Oxygen deficient defects in SiO 2 with different environment are believed to result in different UV bands. 9 Tong et al observed adjustable UV emission bands from silicon rich oxide films. 23 Kim et al 24 observed an UV PL band at 365 nm from silicon rich oxide layer and ascribed it to the hole trapped E' center.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rise of PL intensity with HP in the Si0 2 :Si/Si system can be related to stress stimulated creation of the -Si-Si-centres in the Si0 2 "bulk" [5]. Above explanation does not exclude, of course, other possible sources of HP -HT induced ultraviolet or visible PL: creation of"oxygen sufficient structures" [9] or of ODC [ 11].…”
Section: Photoluminescence From Ht -Hp Treated Silicon Dioxide Andmentioning
confidence: 99%
“…This may be related to a defect associated with the OH groups. Radiation -induced PL from silica reported for about 2.7 eV (460 rim), 3,1 eV (410 nm) and 4.3 eV (290 nm) is probably related to the presence of an "oxygen deficient center" (ODC) [11].…”
Section: Photoluminescence From Ht -Hp Treated Silicon Dioxide Andmentioning
confidence: 99%